2020
DOI: 10.3389/fmicb.2020.01996
|View full text |Cite
|
Sign up to set email alerts
|

High Aluminum Drives Different Rhizobacterial Communities Between Aluminum-Tolerant and Aluminum-Sensitive Wild Soybean

Abstract: Aluminum (Al)-resistant plant cultivars can recruit beneficial microbes to alleviate the stresses. However, the mechanism of how rhizobacterial communities strengthen Al tolerance of wild soybean has not been addressed. The aim of this study was to investigate the bacterial community structure in the rhizosphere of Al-tolerant (BW69) and Al-sensitive (W270) wild soybean germplasm subjected to three Al concentrations. We analyzed the rhizobacterial communities of the two genotypes by high-throughput sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…In other words, these microbial species might be recruited in the rhizosphere after the loss of function of the SST gene in rice and were likely to help rice resistant to high salt stress. Among them, OTU1 ( Dyella ) has the highest relative abundance, and a previous study has reported that the genus Dyella was enriched in the rhizosphere of metal ion-tolerant soybeans, while there are few reports on the function of this bacterium ( 53 ). The most strongly promoted species of the plants without the SST gene are species that promote plant growth and facilitate phosphorus uptake in plants ( Burkholderiaceae ) or have a role in nitrogen cycling in soil (“ Candidatus Rhizobium”) ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, these microbial species might be recruited in the rhizosphere after the loss of function of the SST gene in rice and were likely to help rice resistant to high salt stress. Among them, OTU1 ( Dyella ) has the highest relative abundance, and a previous study has reported that the genus Dyella was enriched in the rhizosphere of metal ion-tolerant soybeans, while there are few reports on the function of this bacterium ( 53 ). The most strongly promoted species of the plants without the SST gene are species that promote plant growth and facilitate phosphorus uptake in plants ( Burkholderiaceae ) or have a role in nitrogen cycling in soil (“ Candidatus Rhizobium”) ( 54 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant tolerance to aluminum additionally depends on the genetically determined resistance mechanism developed by certain plants by stimulating the secretion of organic acids [ 56 ]. In various research works, the toxic effects of the cationic form of aluminum Al 3+ , which is characteristic of solutions with a pH less than 4 [ 56 , 69 , 71 , 72 ], has been widely noted. For solutions characterized by a pH of more than 5.5, on the other hand, neutrally charged Al(OH) 3 [ 73 ] molecules predominate, which suggests a decrease in toxicity compared to the reactive cationic form.…”
Section: Resultsmentioning
confidence: 99%
“…The organic acids released from plant roots, such as citric acid, oxalic acid, and malic acid, can chelate Al 3+ , thereby alleviating aluminum toxicity ( 63 ). Aluminum stress changed the rhizosphere bacterial communities ( 64 ). When plants are in a stressful environment, root exudates can attract beneficial microbes from the environment, which is called a “cry for help” strategy ( 65 ).…”
Section: Discussionmentioning
confidence: 99%